2014
DOI: 10.7841/ksbbj.2014.29.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Essential Oil of Pinus koraiensis Seed Against Pathogens Related to Acne

Abstract: The purpose of the present research was to evaluate the antimicrobial activity of the essential oil extracted from Pinus koraiensis seed against pathogens related to acne. The essential oil was extracted by steam distillation method. The chemical compositions of essential oil were analyzed by GC-MS. Alpha-pinene (29.87%), D-limonene (19.26%), betapinene (11.19%), beta-myrcene (3.84%), n-hexadecanoi acid (3.2%), beta-caryphyllene (2.72%), and cyclohexene (2.17%) were main components. This essential oil had anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In this study, in P. Koraiensis needles collected in spring, the main compounds in October (fall) and February (winter) were confirmed to be Germacrene D and r-Terpinene, respectively. However, in other studies, the main compounds in fall and winter were α-Pinene [72][73][74] and Limonene [75]. In A. holophylla, in this study, D-Limonene was identified as the main substance in needles in April and February, which corresponds to spring and winter, and 3-Carene in fall.…”
Section: Discussionmentioning
confidence: 46%
“…In this study, in P. Koraiensis needles collected in spring, the main compounds in October (fall) and February (winter) were confirmed to be Germacrene D and r-Terpinene, respectively. However, in other studies, the main compounds in fall and winter were α-Pinene [72][73][74] and Limonene [75]. In A. holophylla, in this study, D-Limonene was identified as the main substance in needles in April and February, which corresponds to spring and winter, and 3-Carene in fall.…”
Section: Discussionmentioning
confidence: 46%
“…Essential oils are highly volatile in the air, and their fragrances vary depending on plant material and species [14]. Specifically, the essential oils are obtained from flowers, buds, seeds, leaves, bark, fruits, and roots [15].…”
Section: Investigating the Selected Pinaceae And Cupressaceae For Ess...mentioning
confidence: 99%
“…The essential oils showed mild antimicrobial properties by inhibiting the growth of other pathogens related to acne. Therefore, it can be used as a natural cosmetic ingredient or as an antimicrobial substance [14].…”
Section: Investigating the Selected Pinaceae And Cupressaceae For Ess...mentioning
confidence: 99%